PENGARUH NAUNGAN DAN INOKULAN MIKORIZA TERHADAP PERTUMBUHAN BIBIT KAKAO PADA TANAH PODSOLIK MERAH KUNING DAN ANDOSOL - Syamsiar Syamsiar (Universitas Tadulako, 2015)
The research of the effect of shading and mycorrhyza inoculations on the growth of cacao seedlings on the Red-yellow Podzolic soil and Andosol had been conducted in Microbiology laboratory of Agriculture Faculty, Gadjah Mada University, and a field experiment in Pogung, subdistrict of Sinduadi, Mlati, Sleman, Yogyakarta. The research aimed to determine the best combination that can increase the quality of the cacao seedling. The research was conducted using a Split-split plot design, the experimen was done with three factors and three replicates. The first factor was the shading level that consisted of no shading, shading in 25%; 50% and 75%. The second factor was the type of soils (red-yellow podzolic soil and andosol), The third factor was the mycorrhyza inoculations (no-mycorrhyza inoculation, Gigaspora margaritainoculation and Glomus manihotis inoculation). Results of this research showed that the interaction effect between the three factors wassignificant. Interaction occurred between the shading and the soil type and also between the shading and the mycorrhyza inoculation, meanwhile each single factor had also significant effect on all variable observed. The interaction between shading and soil significantly affected stem diameter, root dry-weight, root volume, root shoot ratio, relative growth rate (RGR), and P absorption. The interaction between the shading and the mycorrhyza had significant influence on plant height and specific leaf weight (SLW). The shading level of 25% on the andosol soil inoculated with the Glomus manihotismycorrhyza is the best treatment for growing cacao seedlings. Keywords: Andosol, Cacao seedling, Mycorrhyza, Red-yellow Podzolic soil, Shading.